2021
DOI: 10.1002/gps.5628
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of people with dementia lost to follow‐up from a dementia care center

Abstract: Objective: To identify the prevalence and characteristics of people living with dementia (PLWD) lost to follow-up (LTFU) from a specialized dementia care clinic and to understand factors influencing patient follow-up status. Methods:We conducted a retrospective chart review of PLWD seen at a dementia care clinic 2012-2017 who were deceased as of 2018 (n = 746). Participants were evaluated for follow-up status at the time of death. Generalized linear regression was used to analyze demographic and diagnostic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(29 citation statements)
references
References 45 publications
0
29
0
Order By: Relevance
“…The remaining studies were conducted in single countries. Eleven of them were carried out in the USA [ 30 , 32 , 33 , 35 , 37 , 39 , 42 , 43 , 45 47 ], four in Japan [ 36 , 38 , 40 , 51 ], two in Hong Kong (Special Administrative Region), China [ 50 , 52 ], two in South Korea [ 41 , 53 ], and one each in Austria [ 31 ], Canada [ 44 ], Israel [ 49 ], New Zealand [ 54 ] and Spain [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The remaining studies were conducted in single countries. Eleven of them were carried out in the USA [ 30 , 32 , 33 , 35 , 37 , 39 , 42 , 43 , 45 47 ], four in Japan [ 36 , 38 , 40 , 51 ], two in Hong Kong (Special Administrative Region), China [ 50 , 52 ], two in South Korea [ 41 , 53 ], and one each in Austria [ 31 ], Canada [ 44 ], Israel [ 49 ], New Zealand [ 54 ] and Spain [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“… How was LTFU identified? Chronic Mental Disease Berghofer et al (2002) [ 31 ]/ Austria, Cohort Community mental health centres Patients with mental health condition except those with dementia or mental retardation 111 57 (51.4%) Non-LTFU: LTFU : Overall: 41.3 (13.4) 35.9 (12.2) 38.5 (13.0) DNS DNS DNS DNS DNS DNS Defined dropouts as patients who from the clinical point of view need psychiatric treatment, but who discontinue treatment on their own initiative by failing to attend arranged visits at the Community Mental Health Centres during the 4-month study period 4 (Prior analysis indicated stabilisation of service use after 4 months) Self-reported Bowersox et al (2013) [ 32 ]/ USA, Cohort Outpatient Veterans Health Administration care Mood disorder; Psychosis; Substance dependence disorder; Anxiety disorder; Axis II disorder 233 202 (86.7%) Non-LTFU: LTFU : Overall: DNS DNS 49.89 (8.28) DNS DNS DNS DNS DNS DNS Dropped out of care based on a period of 5 weeks or greater without contact with their treatment staff 1 15 (5 weeks) (Validated standard by the Health Plan Employer Data Information set) Electronic medical records Boyd et al (2022) [ 33 ]/ USA, Cohort Memory and Aging Center Dementia 746 314 (42.1%) Non-LTFU: LTFU : Overall: DNS DNS DNS DNS DNS DNS DNS DNS DNS Follow‐up status was determined from the documented follow-up plan at the final in‐person clinic visit. Participants who did not return to clinic 3 or more months after their recommended return date were classified as LTFU ≥ 3 (DNS) <...…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations